Two new labdane diterpenoids and one new β-lactam from the aerial parts of Roylea cinerea. (March 2017) - Sharma, Reena; Mohammadi-Ostad-Kalayeh, Sona; Stahl, Frank; Zeilinger, Carsten; Dräger, Gerald; Kirschning, Andreas; Ravikumar, P.C.
Graphical abstract: Highlights: Two new labdane diterpenoids were isolated and named as cinereanoid C and D. A new β lactam compound was isolated and named as cinerealactam E. All known compounds were isolated for the first time from Roylea cinerea . Hsp90/Hsp70 inhibitory activity of the isolated compounds was investigated. Abstract: Two new labdane diterpenoids cinereanoid C (1 ), cinereanoid D (2 ), a new β -lactam, cinerealactam E (3 ) as well as six known flavonoid glycosides (4–9 ) were isolated from the aerial parts of Roylea cinerea ( Lamiaceae ). The structures of (1–9 ) were all determined by MS, IR and NMR spectroscopy. The structure of cinereanoid D (2 ) was further proven by single crystal X-ray diffraction. Six known flavonoid glycosides (4–9 ) were also isolated for the first time from this plant.2, 5, 6 and7 were found to significantly inhibit the ATP binding of a tumour growth-promoting heat shock protein, Hsp90.